The Needs of the Financial Labour Market in Romania and the Answer of the Local Universities to This Social Demand - Paul Diaconu; Nicoleta Coman; Catalina Gorgan; Vasile Gorgan; Codrina Sandru (Journal of Accounting and Management Information Systems (JAMIS), 2011)
This study is an empirical research that aims to investigate what the labour market for the financial-accounting segment in Romania require in terms of professional and personal skills developed within the accounting education curriculum in the Romanian universities. Also, we investigate if the training of young practitioners in Romanian universities' is appropriate or not from the curricular point of view to the employers' demands. We use a statistical analysis of frequencies, aiming to an importance stratification of the professional and personal characteristics in the employers' demands. The study groups the job ads into three categories: financial accounting, managerial accounting and audit, and seeks to identify specific curriculum descriptors for these categories of professional development. At the same time, we perform a frequency analysis of curriculum descriptors and job execution, comparatively to the management jobs, attempting to design a hierarchy of professional and personal skills, depending on the wording of notices by employers. Our main conclusion is that the curricular programs of Romanian universities in the economical field, though responding in terms of theoretical knowledge, should be extended considering the needs of the practice, particularly in the area of personal skills development, which are very important in a competitive selection process.
Keywords: M41; M14; M49; 650; accounting education curriculum; personal skills; professional skills; ethics; IES's